2014
DOI: 10.14348/molcells.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Feeder-Free Culture System for Expansion of Mouse Spermatogonial Stem Cells

Abstract: Spermatogonial stem cells (SSCs, also called germline stem cells) are self-renewing unipotent stem cells that produce differentiating germ cells in the testis. SSCs can be isolated from the testis and cultured in vitro for long-term periods in the presence of feeder cells (often mouse embryonic fibroblasts). However, the maintenance of SSC feeder culture systems is tedious because preparation of feeder cells is needed at each subculture. In this study, we developed a Matrigel-based feeder-free culture system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Matrigel was a promising candidate because it is commonly used for adherent cultures of pluripotent stem cells, such as human ESCs and human induced pluripotent stem cells. Recently, our group demonstrated that mouse spermatogonial stem cells can also be expanded on Matrigel and maintained in culture for a long time (Choi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrigel was a promising candidate because it is commonly used for adherent cultures of pluripotent stem cells, such as human ESCs and human induced pluripotent stem cells. Recently, our group demonstrated that mouse spermatogonial stem cells can also be expanded on Matrigel and maintained in culture for a long time (Choi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Because of supporting self-renewability and pluripotency, Matrigel is mostly used for in vitro feeder-free cultures of mouse and human embryonic stem cells (ESCs; Xu et al 2001;Amit et al 2004;Ludwig et al 2006). Our recent study showed that spermatogonial stem cells (also called germline stem cells), unipotent spermproducing stem cells in the testis, can be successfully expanded in Matrigel-based feeder-free culture in vitro (Choi et al 2014). Matrigel has been used to enhance survival and differentiation of neural cells derived from mouse and human ESCs Uemura et al 2010;Ramos-Hryb et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“… 33 Matrigel promotes in vitro cell differentiation, but it also provides a critical 3D structure for stem cell culture that allows stem cell expansion without the need for feeder layers. 34 , 35 We exploited these characteristics by introducing Matrigel into the precast thin PCL scaffolds as a way to mimic the in vivo ECM for controlled release of biologics and temporal regulation of cell proliferation and differentiation. The inclusion of Matrigel was critical for the development of hematopoiesis, because the scaffolds without a Matrigel coating showed lower CFUs within the induced ossicles (group 2) when compared with ossicles induced by scaffolds coated with Matrigel (groups 3–5).…”
Section: Discussionmentioning
confidence: 99%
“…During development, extracellular matrix signalling is dynamic, constantly remoulded by proteases and changes in the expression of its different protein components, that initiate or alter various biological processes (Duband & Thiery, 1982;George, Georges-Labouesse, Patel-King, Rayburn, & Hynes, 1993;Page-McCaw, Ewald, & Werb, 2007). Extracellular matrix was also used in stem cell culture for its ability to either induce differentiation or for its characteristics that sustain stem cells, and in some cases, it can replace the feeder cells (Choi et al, 2014;Engler et al, 2006;RasiGhaemi et al, 2019). Poly-L-lysine, which is commonly used to enhance cell adhesion to the surface of cell culture dish (Babic et al, 2008), has several unique biological properties, like its ability to aid cell membrane permeability in murine tumour cells (Debnath, Mukherjee, Karan, Debnath, & Chatterjee, 2018).…”
mentioning
confidence: 99%